Photothermal killing of Staphylococcus aureus using antibody-targeted gold nanoparticles - Millenbaugh NJ (Dove Medical Press, 2015)
Nancy J Millenbaugh,1 Jonathan B Baskin,1 Mauris N DeSilva,1 W Rowe Elliott,1 Randolph D Glickman2 1Maxillofacial Injury and Disease Department, Naval Medical Research Unit San Antonio, Joint Base San Antonio-Fort Sam Houston, TX, USA; 2Department of Ophthalmology, The University of Texas Health Science Center at San Antonio, San Antonio, TX, USAPurpose: The continued emergence of multidrug resistant bacterial infections and the decline in discovery of new antibiotics are major challenges for health care throughout the world. This situation has heightened the need for novel antimicrobial therapies as alternatives to traditional antibiotics. The combination of metallic nanoparticles and laser exposure has been proposed as a strategy to induce physical damage to bacteria, regardless of antibiotic sensitivity. The purpose of this study was to test the antibacterial effect of antibody-targeted gold nanoparticles combined with pulsed laser irradiation.Methods: Gold nanoparticles conjugated to antibodies specific to Staphylococcus aureus peptidoglycan were incubated with suspensions of methicillin-resistant and methicillin-sensitive S. aureus (MRSA and MSSA). Bacterial suspensions were then exposed to 8 ns pulsed laser irradiation at a wavelength of 532 nm and fluences ranging from 1 to 5 J/cm2. Viability of the bacteria following laser exposure was determined using colony forming unit assays. Scanning electron microscopy was used to confirm the binding of nanoparticles to bacteria and the presence of cellular damage.Results: The laser-activated nanoparticle treatment reduced the surviving population to 31% of control in the MSSA population, while the survival in the MRSA population was reduced to 58% of control. Significant decreases in bacterial viability occurred when the laser fluence exceeded 1 J/cm2, and this effect was linear from 0 to 5 J/cm2 (r2=0.97). Significantly less bactericidal effect was observed for nonfunctionalized nanoparticles or functionalized nanoparticles without laser activation.Conclusion: Laser-activated nanoparticles targeted to S. aureus surface antigens significantly reduced the percentage of viable organisms and represents a promising new treatment modality that could be used either alone or as an adjunct to existing, conventional antibiotic therapy. Keywords: MRSA, bacteria, pulsed laser, nanospheres, photoacoustic